2006
DOI: 10.1007/s00330-006-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated vs. manual assessment of left ventricular function in cardiac multidetector row computed tomography: comparison with magnetic resonance imaging

Abstract: We compared semiautomatic contour detection and manual contour tracing in cardiac multidetector row computed tomography (MDCT) with magnetic resonance imaging (MRI) for calculation of left-ventricular (LV) volumes. The study included 30 patients who underwent contrast-enhanced cardiac MDCT and cardiac cine-MRI. Were calculated 8 mm short-axis slices from MDCT data using three-dimensional multiphase image reconstruction. LV volumes including peak ejection rate and peak filling rate were calculated from manually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 16 publications
2
41
1
1
Order By: Relevance
“…In contrast, previous comparative studies on 16-slice and 64-slice CT systems versus MRI revealed a systematic deviation between −3.9±7.5% to 1.8± 4.7% for left-ventricular ejection fraction [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25]. A recent meta-analysis on studies on MDCT left-ventricular function analysis versus MRI in 252 patients revealed a (weighted) average difference of -1.7±3.1% in left-ventricular ejection fraction [35].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast, previous comparative studies on 16-slice and 64-slice CT systems versus MRI revealed a systematic deviation between −3.9±7.5% to 1.8± 4.7% for left-ventricular ejection fraction [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25]. A recent meta-analysis on studies on MDCT left-ventricular function analysis versus MRI in 252 patients revealed a (weighted) average difference of -1.7±3.1% in left-ventricular ejection fraction [35].…”
Section: Discussioncontrasting
confidence: 65%
“…Assessment of global left-ventricular function using 4-, 8-, and 16-slice multidetector computed tomography (MDCT) has been performed in good agreement with cine magnetic resonance imaging (MRI), echocardiography, and ECG-gated single photon emission CT (SPECT). Those single-centre studies revealed a systematic overestimation of left-ventricular end-systolic volumes (ESV), most likely due to limited temporal resolution of the CT system used ranging between 125 to 250 ms [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently, phantom measurements as well as initial clinical experience on left-ventricular function assessment with 64-slice CT [21][22][23][24] and dual-source multidetector CT systems [26,27] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that multi-slice computed tomography can effectively assess the left ventricular function [138,139]. However, the use of this technique for this particular aim is still under evaluation, and various limitations must be considered, such as the use of contrast media, the need for low heart rates during acquisition and the relatively prolonged post-processing [133].…”
Section: Gated Spect Versus Other Imaging Modalitiesmentioning
confidence: 99%
“…For quantitative evaluation of cardiac parameters, slices from the base of the heart to the apex were analyzed. The base of the left ventricle was defined as the most basal slice surrounded by at least 50% myocardium in all cardiac phases [20] and the apex as the last slice with a visible lumen along the entire cardiac cycle. In each patient end-diastolic and end-systolic phases were visually determined and manually marked by the observers as the images showing the largest and smallest LV cavity areas, respectively.…”
Section: Mri Image Acquisition Protocolmentioning
confidence: 99%